Ephestia animella sp. n. (Lepidoptera: Pyralidae, Phycitinae) from the Ural Mountains and southern Siberia - Nupponen, Kari; Junnilainen, Jari (Entomologica Fennica, 1998)
Ephestia animella sp. n. is described from the southern Ural Mountains. It has also been found in the Altai Mountains and Buryatia in southern Siberia. The species occurs in virgin taiga forests from mid-June to early July, and is active only at night. It is a small, dark species that differs from closely related species both externally and by the genitalia. The systematic position of E. animella is discussed.